Characteristics of a Typical Tamarix Hohenackeri Shrub Resource Island in Qaidam Basin Under Prevailing Wind - Gao Siyuan; Cao Guangchao; Diao Erlong; He Qixin; Cheng Mengyuan; Qiu Xunxun; Cheng Guo; Zhao Meiliang (Shuitu baochi tongbao)
[Objective] The characteristics of a typical Tamarix hohenackeri shrub resource island in Nuomuhong area of Qaidan Basin under the action of prevailing winds were studied in order to deeply understand the ecological significance of tamarisk shrubs in similar habitats, and to provide a reference for saline-alkali land improvement and ecological protection of desert-oases. [Methods] Measurements of soil organic carbon (SOC), soil moisture content (SMC), soil pH value, and EC values in different soil layers to a depth of 110 cm at positions under the canopy, at the edge of the canopy, and in open areas were made by systematically sampling the soil surrounding typical tamarisk shrubs in the desert-oasis transition zone in the Nuomuhong area of the Qaidam Basin. [Results] ① The litter and underground biomass around the shrub and under the canopy were significantly greater than at the edge of the canopy in the open space. SOC under the canopy was significantly greater than at the canopy edge, exhibiting the characteristics of a resource island; ② SMC under the canopy in the leeward direction and SOC of the leeward canopy edge and open space were significantly greater than in other directions, and the soil pH values of the 0—5 cm soil layer at the canopy edge were lower; ③ The aboveground biomass and litter at the edge of the canopy were significantly greater in the leeward direction than in other directions, which in turn reduced water evaporation and increased SOC. [Conclusion] The soil around the shrub not only exhibited the characteristics of a resource island under the canopy, but also resulted in SMC, SOC contents, and lower soil pH value that were more suitable for plant growth in the leeward direction, and therefore could be called a resource island in the wind shadow area.